Vote or adstain the effect of repetitive exposure and type of advertisement on the inclination to vote for a presidential candidate - Cadiz, Dominique; Gopalan, Amberly; Guerrero, Amirah; Palpal-Latoc, Moarley; Reyes, Chynna (2021)
Access online through this link: https://journals.upd.edu.ph/index.php/Dunong/article/view/8814/7772
Keywords: Political advertising; Presidential elections; Political campaigns